GRAFT COMPATIBILITY BETWEEN EUROPEAN PEAR CULTIVARS AND EAST MALLING “C” ROOTSTOCK COMPATIBILIDADE DE ENXERTIA ENTRE CULTIVARES DE PEREIRAS EUROPEIAS E PORTAENXERTOS DE MARMELEIRO EAST MALLING “C” - Machado B.D. (2017)
© 2017, Sociedade Brasileira de Fruticultura. All rights reserved.Graft incompatibility is one of the main factors limiting european pear production in Brazil. At present, there is no clear indication of the best combination(s) of european pear cultivars and quince rootstocks for graft compatibility. The study evaluated the graft compatibility for combinations of european Abbè Fetel, Rocha and Williams pear cultivars grafted onto the EMC quince rootstock. The experiment was performed in a commercial european pear orchard in the Urupema municipality, in State of Santa Catarina, during the 2011/12, 2012/13 and 2013/14 growing seasons. The plant growth variables comprised the section increment (mm) in the trunk diameter in the graft union region of cultivars and rootstocks; difference in the diameter of the graft for cultivars and rootstocks; “translocated” incompatibility; “located” incompatibility and the vascular connection in the graft union region, which was assessed by immersing the bases of the plants in a 0.08% succinic acid solution. There were “located” and “translocated” incompatibility between the european Williams pear cultivar and the EMC rootstock based on the vascular discontinuity in the graft union region, which prevented the translocation of succinic acid stain. Thus, the Williams/EMC combination is considered incompatible and it is not recommended for use in commercial orchards. The Rocha/EMC and Abbè Fetel/EMC are considered partially incompatible combinations and showed good development eight years after planting.